O surgimento do sistema possessivo do português coloquial: uma interpretação funcional - Perini, Mário A. (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2016)
This paper the organization of possessive phrases in modern Brazilian Portuguese, and attempts to set up a functional hypothesis to explain its emergence in the language. The possessive system of Brazilian Portuguese is assymetrical, and includes, on one hand, possessive pronouns like meu (s) ’my’ for the first person singular and plural, and for the second singular; and on the other hand, analytic forms like de vocês ’your (pl)’ for the second person plural, third singular and third plural. The diachronic emergence of such a system is explained as result of the working of two principles, which are "functional" in the sense that they represent a tendency toward a grammar which is more adapetd to the needs of communication, rather than a grammar whixh is merely simpler. These principles are: One: Ambiguity must be avoided wheneer it precules recovering of the grammatical person referred to. Two: When a system is altered to suit Principle One, onle minimum alterations are allowed.